Perspectives on literature and translation : creation, circulation, reception - Nelson, Brian, 1946-; Maher, Brigid (Brigid Catherine Anne) (New York, NY : Routledge, Taylor & Francis Group, 2013)
'This volume explores the relationship between literature and translation from three perspectives: the creative dimensions of the translation process; the way texts circulate between languages; and the way texts are received in translation by new audiences. The distinctiveness of the volume lies in the fact that it considers these fundamental aspects of literary translation together and in terms of their interconnections. Contributors examine a wide variety of texts, including world classics, poetry, genre fiction, transnational literature, and life writing from around the world. Both theoretical and empirical issues are covered, with some contributors approaching the topic as practitioners of literary translation, and others writing from within the academy'--
Includes bibliographical references and index.
Keywords: Translating and interpreting; Literature -- Translations -- History and criticism